Improving the Effectiveness of Hybrid Learning Through the Computer-Supported Collaborative Learning Model Facing Pandemic Covid-19 (Journal of Namibian Studies : History Politics Culture, 2023)
Hybrid Learning using Computer Supported Collaboration Learning (CSCL) is an effort to maximize learning during the Covid-19 pandemic. This study aims to increase the effectiveness of implementing hybrid learning using CSCL in dealing with  COVID-19. The research method uses qualitative case studies, and the data is processed using interactive data analysis from Miles and Huberman.   The results showed: 1) CSCL  learning is a very appropriate model applied to blended learning during the Covid-19 pandemic, this model is  able to improve student learning outcomes,  students study harder,  active, focused, learn quickly,    discuss and cooperate in groups, have confidence,   manage learning time and help each other in their groups; 2)   The CSCL model is more effective compared to conventional learning models because it can create a more active, creative and innovative learning atmosphere; 3) CSCL learning during face-to-face classes is better able to improve student performance and creativity and innovation in learning compared to implementing CSCL in online learning, because students can discuss and cooperate directly; 4) CSCL learning is able to improve student learning outcomes, this condition can be seen from the assignment scores and midle test and final test grades; 5) CSCL learning is able to improve students' ability to discuss and collaborate in groups; 6) CSCL learning is able to overcome the limited internet network in Higher Education.